2016
DOI: 10.1039/c5tb02780b
|View full text |Cite
|
Sign up to set email alerts
|

Combination assay of lung cancer associated serum markers using surface-enhanced Raman spectroscopy

Abstract: A highly sensitive and specific SERS-based combination assay of lung cancer associated serum markers is reported, and the LODs of CEA and NSE in human serum specimens are 1.48 pg mL−1 and 2.04 pg mL−1, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 30 publications
0
26
1
Order By: Relevance
“…The sensitivity to the environment of the NPs and interparticles coupling enables the uses of LSPRs in biosensing applications [67,68]. Besides, LSPRs are able to greatly amplify the local electromagnetic (EM) fields, making the Au NPs ideal for use in SERS [69,70,71,72,73,74] and MEF [75,76,77]. The small mode volume of LSPRs also increases the photonic local density of states, which can modify the decay rate and quantum efficiency of emitters in the vicinity of Au NPs [78].…”
Section: Optical Diagnostic Based On Au Nanoparticlesmentioning
confidence: 99%
“…The sensitivity to the environment of the NPs and interparticles coupling enables the uses of LSPRs in biosensing applications [67,68]. Besides, LSPRs are able to greatly amplify the local electromagnetic (EM) fields, making the Au NPs ideal for use in SERS [69,70,71,72,73,74] and MEF [75,76,77]. The small mode volume of LSPRs also increases the photonic local density of states, which can modify the decay rate and quantum efficiency of emitters in the vicinity of Au NPs [78].…”
Section: Optical Diagnostic Based On Au Nanoparticlesmentioning
confidence: 99%
“…An ultrasensitive SERS substrate was developed for the detection of multiple microRNA (miRNA) biomarkers for lung cancer using molecular beacons attached to the surface of an Ag nanorod array. This sensor was able to detect attomolar concentrations of the miRNA sequences in human serum, creating the potential for use of this substrate as a clinical lung cancer detection mechanism [ 102 , 103 ].…”
Section: Cancermentioning
confidence: 99%
“…This technique was modified further to enable multiplexed detection through the preparation of two different nanotags, containing different Raman reporter molecules and antibodies for either CEA or neuron-specific enolase (NSE). These nanotags were placed in solution with Au-coated magnetic nanoparticles (Fe 3 O 4 , GMNP) and functionalized with antibodies to both biomarkers, creating a sandwich assay with a unique reporter molecule signal for each biomarker [ 102 ]. The LODs were reported as 1.48 and 2.04 pg mL −1 for CEA and NSE, respectively, demonstrating their potential utility as a clinical tool for lung cancer diagnostics.…”
Section: Cancermentioning
confidence: 99%
“…Recently, surface-enhanced Raman scattering (SERS) based methods for multiple tumor biomarkers detection have got a lot of attentions because of its narrow 'fingerprint' Raman spectrum from analyte molecule, which enables the SERS to be utilized to recognize and quantify various targets from mixture [31]. With the development of various nanomaterials, SERS was utilized for detecting multiple cancer biomarkers successfully [32][33][34][35][36]. For example, in order to detect AFP and Glypican-3, Tang et al has used silver nanoparticle film as SERS substrate to design SERS frequency-shift immunoassay [32].…”
mentioning
confidence: 99%
“…For example, in order to detect AFP and Glypican-3, Tang et al has used silver nanoparticle film as SERS substrate to design SERS frequency-shift immunoassay [32]. By taking advantages of gold nanoflowers and SERS-active magnetic nanoparticles, a sandwich immunoassay was designed by Song et al to detect CEA and NSE, which showed high specificity and sensitivity [33]. Li et al designed an innovative SERS technique using branched DNA-gold nanoaggregates to detect MUC1mucin and nucleolin on breast cancer cell surface [34].…”
mentioning
confidence: 99%